2019
DOI: 10.1111/bpa.12720
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐exome sequencing revealed mutational profiles of giant cell glioblastomas

Abstract: Giant cell glioblastoma (gcGBM) is a rare histological variant of GBM, accounting for about 1% of all GBM. The prognosis is poor generally though gcGBM does slightly better than the other IDH‐wild‐type GBM. Because of the rarity of the cases, there has been no comprehensive molecular analysis of gcGBM. Previously, single‐gene study identified genetic changes in TP53, PTEN and TERT promoter mutation in gcGBM. In this report, we performed whole‐exome sequencing (WES) to identify somatically acquired mutations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
2
11
0
Order By: Relevance
“…Therefore, this study suggests that ultra-mutated GBMs might represent a subgroup of giant cell GBMs, which is not only characterized by POLE mutations. However, giant cell enrichment is not a unique feature of ultra-mutated GBMs and no ultra-mutated cases were found in a cohort of giant cell GBMs in a recent study [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study suggests that ultra-mutated GBMs might represent a subgroup of giant cell GBMs, which is not only characterized by POLE mutations. However, giant cell enrichment is not a unique feature of ultra-mutated GBMs and no ultra-mutated cases were found in a cohort of giant cell GBMs in a recent study [32].…”
Section: Discussionmentioning
confidence: 99%
“…No information is available regarding the specific molecular or phenotypic characteristics of LS-(or CMMRD)-related brain tumors. The histological variant of glioblastoma with multinucleated giant cells is also not specific [106,108,109], but given its rarity (approximately 1% of all glioblastomas), there may be a particular interest in proposing a constitutional MMR gene (and POLE) analysis in patients with a giant cell glioblastoma.…”
Section: Brain Tumorsmentioning
confidence: 99%
“…A previous whole genome sequencing study identified the TERT promoter as the only non-coding region that is recurrently mutated in medulloblastoma [45]. Accordingly, we performed Sanger sequencing to evaluate the mutational hotspots of TERT promoter, C228T and C250T (124 and 146 bp upstream of the ATG start site respectively), as previously described [1,8,9,37,64,71,72].…”
Section: Sanger Sequencing For Tert Promoter Hotspot Mutationsmentioning
confidence: 99%